2021
DOI: 10.1007/s40996-021-00682-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors and Interactions that Influence the Pressure Drop Across An Air Volume Reducing Device on Low-Pressure Water Distribution Networks

Abstract: Efficient water supply systems are necessary for the development and sustainability of human societies. One relevant aspect of these systems is the metering function, recorded employing water meters, which determines the charges levied to the clients and estimates the water losses in the network. Inaccurate measurements are detrimental for both the client and the supplier. For allowing more precise metering, one option is to use an air volume reducing device, an accessory similar to a check valve that minimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…To carry out the study in a controlled manner, an initial pressure value was set as an input border doncicion with a value of 300 kPa, characteristic value in aqueduct tubers as observed in a study by Carpintero et al, [7], this for all treatments, since in CFD simulations for fluid flows, the pressure should be indicated as the input boundary, and the flow rate should be indicated as the output boundary for this type of study.…”
Section: Fig 1 Geometry Of the Studied Globe Valve Units In MMmentioning
confidence: 99%
See 1 more Smart Citation
“…To carry out the study in a controlled manner, an initial pressure value was set as an input border doncicion with a value of 300 kPa, characteristic value in aqueduct tubers as observed in a study by Carpintero et al, [7], this for all treatments, since in CFD simulations for fluid flows, the pressure should be indicated as the input boundary, and the flow rate should be indicated as the output boundary for this type of study.…”
Section: Fig 1 Geometry Of the Studied Globe Valve Units In MMmentioning
confidence: 99%
“…CFD tools also contribute to cost reduction in development and testing, as adjustments can be made in a computational environment to achieve the expected results, thereby improving the performance and safety required by the design. Additionally, the application of Design of Experiments (DOE) in fluid mechanics aids in the analysis of developed tests, providing a valuable assessment of fluid behavior in simulated systems and optimizing performance efficiently and effectively, as indicated in previous studies [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In other related studies, contact friction is designed analytically in the involute of gears, as well as the simulation of non-newtonian liquids, CFD applications, DOE design of experiments, and remeshing in deformable systems by finite elements, as also indicated in Ref. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The transition from conventional energy transformation methods to the use of renewable energies invites us to venture into new ways of generating energy through increasingly cleaner sources [1][2][3]. As is the use of biomass material, which, being a residue of agro-industrial processes, can be used for energy generation as indicated in previous studies [4,5].…”
Section: Introductionmentioning
confidence: 99%